Serological status of cattle to bovine viral diarrhoea virus and bovine herpesvirus 1 at entry to and exit from Australian feedlot backgrounding facilities. Issue 1 (2nd October 2020) - Cusack, PMV; Bergman, EL; Hay, KE; Morton, JM
Abstract : A total of 6195 cattle were enrolled in this observational study. Serum antibody concentrations to bovine herpesvirus 1 (BHV1) and bovine viral diarrhoea virus (BVDV) were measured at entry to and exit from backgrounding facilities to assess their statuses on arrival and the extent of seroconversion to these viruses during backgrounding. The backgrounding facilities were contiguous with five feedlots in: Queensland (two sites), New South Wales, South Australia and Western Australia. Cattle were held in the backgrounding facilities for a minimum of 29 days and a median of 34 days. On backgrounding facility entry, 32.7% of the study population was seronegative to BVDV, but 85.7% was seronegative to BHV1. After commingling in the backgrounding facilities, of the cattle that were seronegative on backgrounding facility entry, 33.9% and 30.3% showed a serological increase to BVDV and BHV1, respectively. At backgrounding facility exit, when cattle were placed in their feedlots, 19.6% and 59.1% were seronegative to BVDV and BHV1, respectively, and 0.26% were persistently infected with BVDV. There was a strong association between seroincrease to BVDV and seroincrease to BHV1 (P = 0.005) at animal level in cohorts known to contain an animal persistently infected with BVDV.